IDENTIFIKASI SPESIES KATAK BERDASARKAN KARAKTER MORFOLOGI DALAM PEMBELAJARAN PROJECT BASED LEARNING (PJBL) UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI SMA NEGERI 1 LANGOWAN - Mege, Revolson A; Sakul, Ernest H; Balansa, Hendra (Universitas Negeri Manado, 2020)
This study aims to determine the effect of the Project Based Learning Model through practicum identification of frog species based on morphological characters on student learning outcomes in Biology subjects. The Learning Model used in this study is a Project Based Learning Model. The population in this study were all class X students of SMA Negeri 1 Langowan while the sample used was class X MIPA 1 as an experimental class, and class X MIPA 3 as a control class. Data collection techniques using learning outcomes with test instruments in the form of multiple choice questions and descriptions. Data analysis begins with testing the analysis prerequisites, namely tests of normality and homogeneity. Then proceed with hypothesis testing. The results showed the mean of control class learning outcomes = 76.86 while the average learning outcomes of the experimental class = 82.46. The results of the study were analyzed using T-test statistics at a significant level of 0.05 and the results obtained were Tcount = 4.37> Ttable = 2.01 so that H0 was rejected and H1 was accepted. Based on these results it can be concluded that the Project Based Learning learning model can improve student learning outcomes.Keywords: Project Based Learning, Learning Outcomes, Biology Subjects